Featured Cover. (2nd September 2021) - Tan, Samson; Weinert, Darryl; Joseph, Paul; Moinuddin, Khalid A. M.
Abstract : The cover image is based on the Original Article Incorporation of technical, human and organizational risks in a dynamic probabilistic fire risk model for high‐rise residential buildings by Samson Tan et al., https://doi.org/10.1002/fam.2872 .